PEMBELAJARAN DISCOVERY PADA MATERI SIFAT-SIFAT CAHAYA TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS V - Widyastuti, Widyastuti; Jayadinata, Asep Kurnia; Panjaitan, Regina Lichteria (Jurnal Pena Ilmiah, 2017)
Concept which exsist in natural science learning will easier understood by students if the concept followed by experiments to proved about the concept. Emphasize the Science Process Skill, for maximizing students petential mixed up with discovery learning process. Learning models which support Science Process Skill was discovery model learning. This research method applying was pre-experimental method with one group pretest-posttes design. The purpose of this research to checked the improved Science process Skill with applying discovery model learning toward students skill at advanced group, middle-group, and menial group. Population was fifth grade students about Cimalaka Subdistriction Sumedang Regency. Sample is Margamukti Elementaru School. Instruments were KAIPA test, Science Process Skill test, teacher and students activity observation, questionnaire, and interview. Result found that applying discovery model improved students Science Process Skill at advance group, middle-group, and menial group. Had different improved Science Process Skill between advance group, middle group, and medial group.Â